Bone marrow CD73+ mesenchymal stem cells display increased stemness in vitro and promote fracture healing in vivo - Kenichi Kimura; Martin Breitbach; Frank A. Schildberg; Michael Hesse; Bernd K. Fleischmann (Bone Reports, 2021)
Mesenchymal stem cells (MSCs) are multipotent and considered to be of great potential for regenerative medicine. We could show recently (Breitbach, Kimura et al. 2018) that a subpopulation of MSCs as well as sinusoidal endothelial cells (sECs) in the bone marrow (BM) of CD73-EGFP reporter mice could be labeled in vivo.We took advantage of this model to explore the plasticity and osteogenic potential of CD73-EGFP+ MSCs in vitro and their role in the regenerative response upon bone lesion in vivo. Herein we show that isolated CD73-EGFP+ MSCs displayed more pronounced stemness and stronger in vitro differentiation capacity into the osteogenic lineage compared to CD73-EGFP− MSCs. In a bone fracture model, endogenous BM-resident CD73-EGFP+ MSCs were found to migrate to the fracture site and differentiate into cartilage and bone cells. Our analysis also showed that CD73-EGFP+ sECs contributed to the neovascularization of the fracture site. In addition, grafting of CD73-EGFP+ MSCs into acute bone lesions revealed their capacity to differentiate into chondrocytes and osteocytes in vivo and their contribution to callus formation in the regeneration process of fracture healing. Thus, CD73+ MSCs display enhanced stemness and osteogenic differentiation potential in vitro and in vivo illustrating a prominent role of the CD73+ MSC subpopulation to promote fracture repair.